KLASIFIKASI MODEL PEMIKIRAN ORIENTALIS HADIS PERSPEKTIF HERBERT BEERG - Muhammad Asri Nasir; Ahmad Ramzy Amiruddin (IAIN Manado, 2021)
Abstract: The orientalist debate about the authenticity of the hadith was highlighted by Herbert Berg who he specifically described in his work entitled The Development of Exegesis in Early Islam. In the book, Berg made a classification of orientalist thinking models on hadith. Based on this, this article aims to discuss the classification and mention Berg's reasons for placing the orientalists and also explain the implications of Berg's classification in the study of hadith. In this article, the researcher uses descriptive-analytical method by obtaining the following findings: First, there are four models of orientalist thought in Herbert Berg's hadith perspective, namely Early Western Scepticism, Reaction Against Scepticism, Middle Ground, and Renewed Scepticism. Although, as the finding of the research, it was found that from the four models, there are only two models that are relevant to the facts, namely the skeptical and non-skeptic groups. Second, Berg divides the model of thought based on the attitude of the orienalists to hadith. Third, Berg's classification has at least two implications, namely as a method of reading orientalist thinking models on hadith and the creation of a new method in determining the authenticity of hadith, namely the Sanguine Approach and the Skeptical Approach by Berg.. Key Words : Hetbert Berg, Hadith Orientalist, Authenticity of Hadith. Abstrak: Perdebatan para orientalis tentang keotentikan hadis ternyata disorot oleh Herbert Berg yang secara khusus ia gambarkan pada karyanya yang berjudul The Development of Exegesis in Early Islam. Pada buku tersebut, Berg membuat klasifikasi model pemikiran orientalis terhadap hadis. Berdasarkan hal itu, artikel ini bertujuan untuk membahas klasifikasi tersebut serta menyebutkan alasan Berg dalam menempatkan para orientalis tersebut dan juga menjelaskan implikasi klasifikasi Berg dalam kajian hadis. Artikel ini dalam pembahasannya menggunakan metode deskriptif-analitis dengan mendapatkan temuan, sebagai berikut: Pertama, terdapat empat model pemikiran orientalis hadis perspektif Herbert Berg, yaitu Early Western Scepticism, Reaction Against Scepticism, Middle Ground, dan Renewed Scepticism. Meskipun, setelah diteliti ternyatadari keempat model tersebut, hanya ada dua model yang relevan dengan fakta di lapangan, yaitu kelompok skeptis dan non skeptis. Kedua, Berg membagi model pemikiran tersebut berdasarkan sikap ara orientalis terhadap hadis. Ketiga, klasifikasi yang dilakukan Berg setidaknya memiliki dua implikasi, yaitu sebagai metode dalam membaca model pemikiran orientalis terhadap hadis dan terciptanya metode baru dalam menentukan keotentikan hadis, yaitu Sanguine Approach dan Skeptikal Approach oleh Berg. Kata Kunci : Hetbert Berg, Orientalis Hadis, Keotentikan Hadis.